Optimal sovereign debt: An analytical approach - Jean-Charles Rochet (Inter-American Development Bank, Research Department, 2006)
This paper develops a model of sovereign debt where governments are myopic. Instead of focusing on the incentives to repay, as in most of the theoretical literature on the topic (which assumes implicitly that governments have long-term objectives), I therefore consider that governments always repay when they can, but also borrow as much as possible. without paying attention to the burden of future repayments. The pattern of debt is then only determined by the willingness of international investors to lend to the country. I characterize the Rational Expectations Equilibria of the credit market. These equilibria behave like rational bubbles: international investors lend a lot because they anticipate that other investors will lend again in the future. Capital flows are procyclical: the government borrows a fixed proportion of its income until a sudden stop occurs, generating default and an economic crisis. I suggest possible remedies to the high volatility of public expenditures that is generated by such borrowing patterns.
Keywords: 330; Öffentliche Schulden; Internationale Kreditvergabe; Rationale Erwartung; Auslandsschuldendienst; Internationaler Finanzmarkt; Wohlfahrtseffekt; Theorie